Environmental protection European law and governance - Scott, Joanne (Oxford : Oxford University Press, 2009)
The EU has emerged as a major source of innovation in environmental governance. This volume examines EU environmental law and governance, past, present and future. It begins with a broad historical overview of the subject and then considers individual case studies to engage with key issues and specific frameworks.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Environmental law -- European Union countries; Environmental law -- European Union countries -- History; Environmental policy -- European Union countries